THE NEW ROLE AND RISKS OF INTERNAL AUDIT IN THE DIGITAL TRANSFORMATION PROCESS - Xolikov Rаvshаn Аnvаr ogli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
As organizations undergo rapid digital transformation, internal audit functions are being redefined to address emerging technological risks and to provide assurance on digital initiatives. Traditional audit practices must evolve to encompass IT governance, data integrity, cybersecurity, automation, and algorithmic decision-making. This paper explores the transformed role of internal auditors in a digital environment and highlights the new risk landscape that accompanies digital innovation.